Development of a rubric for assessing Multiplicative Thinking in Primary Schools in Zambia - Mungalu, Arthur (Universitas Ahmad Dahlan, 2023)
The study focuses on developing a rubric to assess Multiplicative Thinking (MT) in Zambia. Drawing from a quasi experiment with 3rd to 5th grade students from two schools, the study addressed the question: “What rubric can effectively capture the diverse range of students’ responses to multiplication and division problems in Zambia?”. Inductive content analysis was applied to examine, code and categorise students’ responses to tasks involving reading and drawing patterns, commutative property, daily context, and the inverse relation between multiplication and division. The analysis focused on the Multiplicative Structure of responses using the lens of mutual translation between representation modes. The following categories emerged: no answer, incorrect, partially correct, and correct. The rubric aims to bridge the gap between mathematics education research and practical implementation. Additionally, it aligns with Zambian assessment policy, which promotes rubric use for quality assessment.